THE INFLUENCE OF WORKLOAD ON EMPLOYEE STRESS AT PT ANEKA KARYA TANGGUH PEKANBARU - Yulia Harwina; Mahbubah Srimulatsih (Sean Institute, 2023)
This study aims to determine the effect of workload on employee work stress carried out at PT. VARIOUS WORKS OF TOUGH PEKANBANU. The population in this study was 33 people. In this study, the sample used was the full sample, which was 33 employees. In analyzing the data, this research uses descriptive and quantitative methods. The descriptive method aims to describe the relationship between actual reality and related theories. The results are to be able to draw conclusions and tabulated in tabular form, then analyzed according to research objectives: While quantitative methods are used to determine the relationship between the independent variable (X) and the bound variable M by using statistical equipment simple linear regression method. Based on the t-test Workload obtained tcount 10.210 tabe/ 2.039 The regression equation is V3.547+0.709x Constant of 3.547, meaning that if the Workload the value is 0; then Work Stress has a positive value, which is 3.547 The workload coefficient value (0.709) indicates that every change in Workload increases by 1 unit, the Work Stras period will be nax by 0.709 units. Judging from the coefficient of the workload determinant, it can be explained from the existing R Square (R) value of 0.771 which means that the workload has an effect of 77.1% on employee work stress at PT Aneka Karya Tangguh Pekanbaru. other independent variables not observed in this study .